P57 Implementing a novel clinical pathway for the assessment of obstructive sleep apnoea: integration of clinical decision software with a practice support service team. (11th November 2022) - Chakrabarti, B; Angus, R; Grass, M; Reed, L; England, P; Withington, A; Foster, L; Osborne, M; Adams, S; McKnight, E; Craig, S
Abstract : Background: An increase in referrals for suspected Obstructive Sleep Apnoea (OSA) coupled with the impact of the pandemic threatens to overwhelm NHS Sleep services. The Liverpool Sleep service has implemented a novel pathway incorporating a clinical decision support system (CDSS) utilised remotely using a national call centre, the Practice Support Service (PSS) team. Patient pathway/methodology: The CDSS (SleepHealth Solutions Ltd) is an NHS Framework listed digital ecosystem comprising multiple intelligent consultations encompassing the entire OSA pathway acting as an 'end to end' system solution and an Electronic Patient Record. The PSS team operate remotely accessing a specific component of the CDSS (an 'Initial Review' consultation). 'Suspected OSA' referrals are sent to the PSS team who contact the patient arranging to undertake an 'Initial Review' remotely using the CDSS. This 'Initial Review' consultation generates a completed report placed in a secure digital portal. If indicated, a sleep study is expedited. The CDSS then integrates the sleep study results with the 'Initial Review' generating a final diagnosis which has clinical oversight. Results: Six hundred referrals were received in March 2022 of which 576 (96%) patients were eligible to undertake a consultation with the PSS team. 474 (82%) patients successfully completed the consultation, 42 (7%) did not respond despite 5 attempts at contact, 55 (10%) declined investigation upon being contacted and 5 (1%) could not be contacted on the scheduled appointment time. The mean time from referral receipt to PSS team contacting the patient was 18 working days (with mean time to consultation completion following first patient contact being 8 working days) which was significantly less than prior to PSS pathway implementation (mean 34 (IQR 19) days; McNemar's test; p<0.05) with PSS pathway diagnostic cost savings amounting to £16, 200. 50 patients completed a user experience feedback questionnaire (outlined in table 1 ). Conclusion: The integration of a CDSS within the PSS pathway described here results in timely assessment of suspected OSA, a low 'missed appointment rate', health economic benefit and facilitates remote service delivery whilst resulting in a high level of patient satisfaction. This allows for a scalable community-based model for the assessment of OSA.